Hubungan Penggunaan Gadget Saat Pandemi Covid-19 dengan Ketajaman Penglihatan Siswa - Ni Luh Putu Yunianti Suntari; Gusti Ayu Putri Diah Saraswati; Sipahutar Ida Erni (Jurnal Gema Keperawatan, 2023)
The Covid-19 pandemic in which all countries limit activities that require gathering togothet. So that more communication and meetings are caried out in cyberspace. Many fields are forced to carry out activities online. One of those affected is learning in schools which can no longer be carried out in school building. Online learning directs student to learn through gadgets, such as smartphones, tablets, computer or laptops. The use of gadgets during the Covid-19 pandemic increased dramatically among junior high school students. The use of the gadgets, with duration, frequency, position, and lighting intensity certainly has an impact on visual acuity in children. This study aims to determine the relationship between the use of gadgets and visual acuity during the Covid-19 pandemic in students. The type of research is non-experimental with correlation design and cross sectional design. The sample in this study amounted to 180 people using a probability sampling technique, namely simple random sampling. Data collection uses a questionnaires about the duration of using the gadget via Google Form in WhatsApp and offline data collection. Visual acuity was measured using the Snellen Chart. The results showed that the most age of respondents was 14 years (74.4%), the most gender was male (63,3%), the use of gadgets was classified as always (41,7%), and visual acuity was classified as normal (85,6%). Hypothesis testing using Spearman rank with α = 0.05. There is relationship between the use of gadgets and visual acuity in VIII grade class student with value of p=0,003. The value of r=0,525 shows a strong correlation between gadgets use and the visual acuity of students. Respondents are expected to know the impact of using the wrong gadget, so as not to damage vision health, their eyesight.